Penafsiran QS. Ali Imran Ayat: 55: (Studi Komparatif Penafsiran Al-Qurtubi Dalam Tafsir Jami’ Ahkam Al Qur’an Dan Muhammad Abduh Dalam Tafsir Al Manar) - Khurrotul Aini (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
The interpretation of Jami 'Ahkam al Qur'an is a monumental work by al Qurtubi. With the multi-disciplinary scientific background possessed by al-Qurtubi, it influenced him in interpreting the Qur'an. Likewise, Muhammad Abduh is a figure of renewal in various principles and understanding of Islam. He connects the teachings of religion with modern life, and proves that Islam is not at all contrary to civilization, life and what is called progress. Different approaches and patterns and methodologies that characterize the two interpretations, thus influencing the results of their interpretations, especially in interpreting Q.S Al Imran verse 55. This article intends to present the differences and similarities of interpretations between the two interpreters and their implications in interpretation.